New species of Gelechiidae (Lepidoptera) from Ukraine - Bidzilya, Oleksiy V.; Budashkin, Yury I. (Zootaxa, 2015)
Chrysoesthia halimionella, sp. n., Megacraspedus uzunsyrtus, sp. n., Aristotelia confusella, sp. n., and Dirhinosia interposita, sp. n., are described from Ukraine. Adults and genitalia of the new species are illustrated and compared with related species.